QUALIFICATION OF PHYSICS TEST INSTRUMENTS LIKE-PISA - Rangkuti, Khairina; Bunawan, Wawan (UNIVERSITAS NEGERI MEDAN, 2022)
This research aims to develop a physics test instrument based on scientific literacy PISA (Program for International Student Assessment). Development of test instruments using 4D models (Define, Design, Development, Disseminate). The test instrument was tested by expert validity with a CVI score of 1. The test instrument tested involved 130 participants. The results of the item validity test showed that the 20 items tested were valid with a Cronbach Alpha reliability value of 0.816 (